International Teen Reproductive Health and Development: The Canadian First Nations Context - Mann, Michelle M. (International Indigenous Policy Journal, 2013)
Women’s well-being is dependent on access to reproductive health care. Around the world, however, many women do not have adequate access to this essential health service. Barriers to accessing reproductive health services are especially problematic for Canadian First Nations youth, especially those living in rural and remote communities. This article explores the unique challenges of and approaches to teen reproductive health and sustainable development internationally. The international context of reproductive health and sustainable development can inform and set the context for a discussion of Canadian First Nations teens’ reproductive health. Of special interest is how the United Nations and the international community approached sensitive issues and generated consensus among many different countries, cultures, religions, and customs.